The Disciplining Effect of Credit Default Swap Trading on the Quality of Credit Rating Agencies† - Bonsall, Samuel B.; Koharki, Kevin; Neamtiu, Monica (Contemporary Accounting Research, 2022)
ABSTRACT This study examines whether credit default swap (CDS) trading initiation can serve as a disciplining mechanism for leading credit rating agencies. Specifically, we investigate whether rating agencies improve their rating quality when an alternative source of credit risk information from CDS threatens to expose inaccuracies in their ratings. Understanding potential drivers of credit rating quality is important given the prominence of credit rating agencies as debt market gatekeepers and perceptions that the agencies have underperformed in providing high‐quality credit risk assessments in recent decades. We hypothesize and find that the initiation of CDS trading improves the accuracy of issuer‐paid credit ratings. This evidence is robust to a number of sensitivity tests including alternative ways of measuring rating accuracy and correction for selection bias. We also find that the timeliness of credit ratings, watch list, and outlook placements improves post‐initiation—particularly for negative shocks to credit risk. This study contributes to the credit rating literature by documenting that CDS trading can help discipline rating agencies. It also contributes to the literature studying the implications of the CDS market.